Evaluation of Dietary Fiber, Antioxidant Capacity, Physicochemical Properties, and Consumer Acceptability of a Green Okra (Abelmoschus esculentus L.) Pudding - Armenia Eka Putriana; Damayanthi, Evy; Palupi, Eny; Nasution, Zuraidah; Handharyani, Ekowati (Journal of Health and Nutrition Research, 2025)
Green okra is obtained from the planting process and harvested after 3 months of cultivation. Analysis was carried out in the form of Dietary fiber, Microbial Content, Physical properties tests, and Antioxidant Capacity Analysis. This green okra pudding product study employed a Completely Randomized Design (CRD). The formula comparison treatment was divided into three treatment levels, namely the comparison of mucilage addition (10, 15, and 20 ml). The response variable of this study was the organoleptic properties of okra pudding. There are 3 (three) stages in making green okra pudding, consisting of blanching green okra fruit, extracting green okra (mucilage), and making pudding. Based on the results of this study, the selected green okra pudding formula from the hedonic test is formula 3 which contains 1.24% dietary fiber, no Staphylococcus aureus and contamination by Escherichia coli bacteria is very minimal, pH of 7.21, aroma and texture were rated as typical SNI 01-2891-1992 standard and IC50 result of 24.27% indicates the concentration of the product needed to inhibit 50% of free radical activity, which means that this product has indicating notable antioxidant effectiveness. Conclusion: Green okra pudding with the addition of 20 ml mucilage has the potential to control fasting blood glucose